(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the preparation of nursing students in the face of urgent and emergency care. Methodology: This is a mixed methods study, carried out in a private institution in southern Brazil. For data collection, a sociodemographic questionnaire and a semi-structured questionnaire were applied to a target population of 30 nursing students. Data production took place through a semi-structured interview from July to August 2022. Data were entered into a spreadsheet in the Microsoft Office Excel 2019 program and analyzed using descriptive and inferential statistics. Results: There was a greater predominance of females with a mean age of 18 to 45 years, it was identified that most participants still do not feel prepared to perform urgent and emergency care. Conclusion: it is concluded that during the consultations the students feel insecure and report fear and insecurity of not being able to provide the service. The most cited reasons were: lack of experience and skill in this area, given that urgent and emergency situations require agility, which they reported not having acquired in class.